Electrical Transport Properties of Vanadium‐Doped Bi2Te2.4Se0.6. Issue 1 (8th July 2020) - Riha, Christian; Düzel, Birkan; Graser, Karl; Chiatti, Olivio; Golias, Evangelos; Sánchez-Barriga, Jaime; Rader, Oliver; Tereshchenko, Oleg E.; Fischer, Saskia F.
Abstract : Vanadium‐doped Bi2– x Te2.4 Se0.6 single crystals, with x  = 0.015 and 0.03, are grown by the Bridgman method. Bandstructure characterization by angle‐resolved photoemission spectroscopy (ARPES) measurements shows gapless topological surface states for both vanadium concentrations. The Van‐der‐Pauw resistivity, the Hall charge carrier density, and the mobility in the temperature range from 0.3 to 300 K are strongly dependent on vanadium concentration, with carrier densities as low as 1.5 × 10 16  cm −3 and mobilities as high as 570 cm 2  V −1 s −1 . As expected for transport in gapless topological surface states, the resistivity, carrier density, and mobility are constant below 10 K. The magnetoresistance shows weak antilocalization for both vanadium concentrations in the same temperature range. The weak antilocalization is analyzed with the Hikami–Larkin–Nagaoka model, which yields phase‐coherence lengths of up to 250 nm for x  = 0.015. Abstract : Single crystals of V x Bi2− x Te2.4 Se0.6 with a vanadium concentration of x  = 1.5% and 3.0% are investigated. Photoemission spectroscopy shows gapless topological surface states. The electrical transport properties are strongly dependent on vanadium concentration, and show how transport by bulk and topological surface states are intertwined. The magnetoresistance shows weak antilocalization with phase‐coherence lengths of up to 250 nm.